Loss of Jab1 in Osteochondral Progenitor Cells Severely Impairs Embryonic Limb Development in Mice. Issue 11 (November 2014) - Bashur, Lindsay A.; Chen, Dongxing; Chen, Zhijun; Liang, Bojian; Pardi, Ruggero; Murakami, Shunichi; Zhou, Guang
<x xml:space="preserve">Abstract</x> The transcriptional cofactor Jab1 controls cell proliferation, apoptosis, and differentiation in diverse developmental processes by regulating the activity of various transcription factors. To determine the role of Jab1 during early limb development, we developed a novel Jab1flox/flox; Prx1‐Cre conditional Knockout (cKO) mutant mouse model in which Jab1 was deleted in the osteochondral progenitor cells of the limb buds. Jab1 cKO mutant mice displayed drastically shortened limbs at birth. The short‐limb defect became apparent in Jab1 cKO mutants at E15.5 and increasingly worsened thereafter. By E18.5, Jab1 cKO mutant mice exhibited significantly shorter limbs with: very few hypertrophic chondrocytes, disorganized chondrocyte columns, much smaller primary ossification centers, and significantly increased apoptosis. Real‐time RT‐PCR analysis showed decreased expression of Sox9, Col2a1, Ihh, and Col10a1 in Jab1 cKO mutant long bones, indicating impaired chondrogenesis. Furthermore, in a micromass culture model of early limb mesenchyme cells, alcian blue staining showed a significant decrease in chondrogenesis in Jab1 cKO limb bud cells. The expression of Sox9 and its downstream targets Col2a1 and Aggrecan, as well as BMP signaling downstream targets, Noggin, Id1, and Ihh, were significantly decreased in Jab1 cKO micromass cultures. Moreover, over‐expression of SOX9 in Jab1 cKO micromass cultures partially restored Col2a1and Aggrecan expression. Jab1‐deficient micromass cultures also exhibited decreased BMP signaling response and reduced BMP‐specific reporter activity ex vivo. In summary, our study demonstrates that Jab1 is an essential regulator of early embryonic limb development in vivo, likely in part by co‐activating Sox9 and BMP signaling. J. Cell. Physiol. 229: 1607–1617, 2014. © 2014 Wiley Periodicals, Inc.